Task force of risk assessment for food safety in Vietnam: Operational research to assist policy and capacity building - Hung Nguyen-Viet (International Livestock Research Institute, 2015)
Food-borne disease is a major public health issue in Vietnam. The contamination of popular foods such as pork and vegetables can occur all along the food chain. It is important to understand how and where food safety issues arise to mitigate and prevent food-borne diseases. In Vietnam, risk assessment is an innovative tool for managing food safety, however it is rarely applied and the capacity for application is still lacking. Here we describe the development of a national taskforce for food safety risk assessment to assist policy makers and researchers in managing food safety issues. A taskforce of risk assessment for food safety was formed and consists of researchers in Vietnam working on risk assessment and food safety, and representatives of the Ministry of Health (MOH) and Ministry of Agriculture and Rural Development (MARD). The taskforce first analysed the situation of food safety policy in Vietnam. Key constraints and areas where research and development interventions could assist policy were identified. Stakeholder workshops were conducted to determine scope of activities and prioritize food safety issues. A series of hands-on training with a focus on case studies of risk assessment for food safety were organised to strengthen the risk assessment capacity of taskforce members and of policy makers. Case studies were conducted to (i) assess health risks of vegetables and fish grown/caught in wastewater; (ii) assess health risks related to antibiotic residues in pork; and (iii) interact with stakeholders, disseminate research results and advocate for the use of risk assessment as a tool for food safety management. Health risks from these case studies were quantitatively assessed and risk communication and management strategies developed. Achievements of the task force to date include handson training of policymakers, line managers, and researchers; case studies of risk assessment that were published in a special edition in a Vietnamese journal; and creation of policy briefs. The taskforce was also requested to run training for veterinary professionals of MARD and plans to become a technical group in risk assessment recognized nationally by MOH and MARD. Our next step was to enable risk-based approaches to be easier to use and adaptable to the local context. The taskforce could benefit from the support of ministries, for example, in its institutionalization and subsequently in supporting a series of training for taskforce members and policy makers.